1996
DOI: 10.1007/s004410050535
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic cell death in the rat adrenal gland: an in vivo and in vitro investigation

Abstract: Adrenocortical cell apoptosis was studied by using an established in vivo model, the hypophysectomized rat, and an in vitro model, viz., rat adrenal glands in short-term organ culture. In vivo, apoptosis (biochemical autoradiographic analysis of internucleosomal DNA cleavage) was weak and not apparent until 12-24 h after hypophysectomy. In situ histochemical localization of 3'-end DNA strand breaks revealed that apoptosis in vivo occurred nearly exclusively in subpopulations of zona reticularis cells. Adrenoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 24 publications
2
18
0
3
Order By: Relevance
“…In addition, the evidence for the remodeling of the vasculature after hypophysectomy reinforces the observation that POMC peptides are also required for the maintenance of adult cortical vasculature (Thomas et al 2003). Finally, in contrast to the results of short-term adrenal culture (Carsia et al 1996), the susceptibility of the ZG to triggered cell death is similar to that of other regions. The anti-apoptotic action of ACTH is expected, but the efficiency of the synthetic N-POMC 1-28 is noteworthy.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, the evidence for the remodeling of the vasculature after hypophysectomy reinforces the observation that POMC peptides are also required for the maintenance of adult cortical vasculature (Thomas et al 2003). Finally, in contrast to the results of short-term adrenal culture (Carsia et al 1996), the susceptibility of the ZG to triggered cell death is similar to that of other regions. The anti-apoptotic action of ACTH is expected, but the efficiency of the synthetic N-POMC 1-28 is noteworthy.…”
Section: Discussionsupporting
confidence: 63%
“…10,18,19 Nevertheless, it is still not clear whether (1) the adult adrenocortical zones are maintained by independent proliferation of cells within a zone, (2) the ZG and ZF/ZR are maintained separately by stem cells located at the border between the ZG and ZF (ZI/ZU in the rat), or (3) the entire cortex is maintained by centripetal migration of cells from a peripheral stem cell population located either within the capsule, or the subcapsular region of the ZG. 20,21 A recent study has suggested a variant of the third possibility involving two populations of embryonic adrenocortical progenitors, both of which are capable of generating all the steroidogenic cell types in the adrenal cortex.…”
Section: Resultsmentioning
confidence: 99%
“…DMBA-induced apoptosis has recently been observed in rat adrenal zona reticularis (Tsuta et al 2001), and also in pre-B cells cocultured with bone marrow stromal cells from AhR-null mice (but not from CYP1B1-null mice), indicating a need for CYP1B1 (Heidl et al 1999). Cells undergoing spontaneous apoptosis are found mainly in the zona reticularis of rat (Wyllie et al 1973;Zajicek et al 1986;Carsia et al 1996;Mitani et al 1999;Tsuta et al 2001). Given the fact that adrenal CYP1B1 is induced both by the AhR-agonist PCB 126 (Pang et al 1999) and by ACTH (Brake et al 1999), focal CYP1B1-catalysed DMBA binding in the zona reticularis may therefore occur in cells programmed to undergo apoptosis (Nebert et al 2000).…”
Section: Discussionmentioning
confidence: 98%